9514 1404 393
Answer:
470.16 cm²
Step-by-step explanation:
The apothem of the base is used for two purposes: to find the area of the base, and to find the slant height of each face.
The apothem of the base for side length s is ...
s/2 = a·tan(π/8)
a = s/(2·tan(π/8)) ≈ 7.24 cm
The slant height of a triangular face is found using the Pythagorean theorem. The apothem of the base and the height are legs of the right triangle whose hypotenuse is the slant height. For slant height x, we have ...
x² = 10² + a² = 100 +52.46
x ≈ √152.46 ≈ 12.35
__
The area of the 8 triangular faces will be ...
A = 1/2Px . . . . where P is the perimeter of the pyramid
The area of the base will be ...
A = 1/2Pa
So, the total surface area is ...
A = 1/2P(a + x) = (1/2)(8)(6 cm)(7.24 +12.35 cm) ≈ 470.16 cm²
Answer:
a. 0.6588
b. 0.3978
c. 0. 279
Step-by-step explanation:
In the given question the success and failure are given the number of outcomes is fixed so binomial distribution can be applied.
Here success= p = 12 % or 12/100 = 0.12
failure = q= 1-p = 1-0.12 = 0.88
n= 10
Using binomial probability distribution
a. Probability that the number of selected adults saying they were too young is 0 or 1 is calculated as:
P (x=0,1) = 0.12 ⁰(0.88)¹⁰10 C0 + 0.12 (0.88)⁹ 10 C1= 1* 0.279 * 1 + 0.12 ( 0.3165) 10 = 0. 279 + 0.3978= 0.6588
b. Probability that exactly one of the selected adults says that he or she was too young to get tattoos is calculated as
P (x=1) = 0.12 (0.88)⁹ 10 C1= 0.12 ( 0.3165) 10 = 0.3978
c. Probability that none of the selected adults say that they were too young to get tattoos is
P (x=0) = 0.12 ⁰(0.88)¹⁰10 C0 = 1* 0.279 * 1 = 0. 279
Answer:
The p-value would be 0.0939
Step-by-step explanation:
We can set a standard t-test for the Null Hypothesis that
The test statistic then takes the form
with this value we then can calculate the probability that is left to the right of this value . From theory we know that t follows a standard normal distribution. Then which is smaller than the p-value set by Breyers of 0.10
Answer:
x>-4
Step-by-step explanation:
divide both sides by -6 without changing the sign
Answer:i think its the first one
Step-by-step explanation:
Nothing else makes sense